Factors associated with treatment escalation among MS specialists and general neurologists: Results from an International cojoint study - Saposnik, G; Andhavarapu, S; Fernández, Ó; Kim, H J; Wiendl, H; Foss, M; Zuo, F; Havrdová, E K; Celius, E; Caceres, F; Magyari, M; Bermel, R; et al. (Multiple sclerosis and related disorders, 2022)
BACKGROUND: Previous studies in multiple sclerosis (MS) showed that therapeutic inertia (TI) affects 60-90% of neurologists and up to 25% of daily treatment decisions. The objective of this study was to determine the most common factors and attribute levels associated with decisions to treatment escalation in an international study in MS care. METHODS: 300 neurologists with MS expertise from 20 countries were invited to participate. Participants were presented with 12 pairs of simulated MS patient profiles described by 13 clinically relevant factors. We used disaggregated discrete choice experiments to estimate the weight of factors and attributes affecting physicians' decisions when considering treatment selection. Participants were asked to select the ideal candidate for treatment escalation from modest to higher-efficacy therapies. RESULTS: Overall, 229 neurologists completed the study (completion rate: 76.3%). The top 3 weighted factors associated with treatment escalation were: previous relapses (20%), baseline expanded disability status scale [EDSS] (18%), and MRI activity (13%). Patient demographics and desire for pregnancy had a modest influence (≤ 3%). We observed differences in the weight of factors associated with treatment escalation between MS specialists and non-MS specialists. CONCLUSIONS: Our results provide critical information on factors influencing neurologists' treatment decisions and should be applied to continuing medical education strategies.
Keywords: recidiva; Neurologists; Recurrence; Female; Specialization; Pregnancy; Humans; ženské pohlaví; roztroušená skleróza; lidé; Multiple Sclerosis; specializace; těhotenství; neurologové